Adapting to Climate Change: Assessing Future Residential Energy Demands for Different Climate and Occupancy Scenarios in Turkey - Ahunur Aşıkoğlu Metehan; Aslıhan Şenel Solmaz; Okan Gök; Ayça Tokuç (Buildings)
A significant amount of existing building stock needs renovation to reach nearly zero energy building (nZEB) status with minimal intervention. This paper aims to research and form a basis for future studies to build upon regarding the additional renewable energy requirements for existing buildings under future climate change. The objectives are to investigate the effect of the changing energy requirements in different current and future regional climates, the change in the number of occupants, and the required additional renewable energy. The case building is modeled on an apartment scheme built in different climatic regions. The method is the Transient System Simulation Tool (TRNSYS) building energy simulation to evaluate both the contemporary and changing weather conditions for 2050 according to three Intergovernmental Panel on Climate Change (IPCC) scenarios for 2.6, 4.5, and 8.5 degrees of temperature increase. The integration of required renewable energy and occupancy size with climate change scenarios for various climates fills a gap in the existing research. The results show that while each climatic region responds differently to climate change scenarios, climates that currently have more cooling demands are impacted the most adversely. However, there is no need to change the amount of additional renewable energy installed for 2050.